Pixel Value Differencing and Modulus Function Method for embedded message in Digital Images - Zonyfar, Candra; Ahmad Baihaqi, Kiki; Bela Pertiwi, Annisa (International Journal of Psychosocial Rehabilitation, 2020)
Image steganography is technique hiding messages into digital images so that secret message unvisually. This research discusses of steganography apply by modulus function algorithm and pixel value differencing (PVD) algorithm. We carried out public datasets image 256x256 and 512x512 constituent. Messages could be embedded in the form of text characters of a certain length. Modulus function and pixel value differencing algorithm manages to hide the message so that no change is seen between the cover object and the cross-sectional image. This research was proven to be successful in the process of recovering secret messages. Evaluation were made using peak signal to noise ratio, mean square error, normalized cross correlation and structural content. From the experimental results, measurement value is based on the level of similarity between cover image and stego object with modulus function method is better with an average normalized cross correlation and structural content 1.0000 and 0.999543 respectively.